2x+6/x-9=0

Simple and best practice solution for 2x+6/x-9=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+6/x-9=0 equation:


D( x )

x = 0

x = 0

x = 0

x in (-oo:0) U (0:+oo)

2*x+6/x-9 = 0

2*x^1+6*x^-1-9*x^0 = 0

(2*x^2-9*x^1+6*x^0)/(x^1) = 0 // * x^2

x^1*(2*x^2-9*x^1+6*x^0) = 0

x^1

2*x^2-9*x+6 = 0

2*x^2-9*x+6 = 0

DELTA = (-9)^2-(2*4*6)

DELTA = 33

DELTA > 0

x = (33^(1/2)+9)/(2*2) or x = (9-33^(1/2))/(2*2)

x = (33^(1/2)+9)/4 or x = (9-33^(1/2))/4

x in { (9-33^(1/2))/4, (33^(1/2)+9)/4}

x in { (9-33^(1/2))/4, (33^(1/2)+9)/4 }

See similar equations:

| 8x^2-38x-10=0 | | .3(x-2)+.4x=.2(x-6) | | 2(x-4)=5/6(x+6)-6 | | 3x-23=97-9x | | 1/5(y+2)=1/10y+3/5 | | 2x-4+7=-6x+41 | | 3x-2(x-4)=8-2x+15 | | -3-4x=5x+24 | | 5-(1/2)x=(1/8)x | | 5x^2-4x+3=6 | | 11c=9c+14 | | 2-2x-5/5=x+9/4 | | 12x-3x-7=11 | | 56-s=45-9 | | 1+(3*7)=z | | 1+(3*7)= | | 1/2-1=1/44 | | -24p^2q^2+(-2pq)+3= | | 2x-6x+21=-13 | | -4x+21=-13 | | 28x+4+7x+7=102 | | 1xy=78 | | 1*y=787 | | 1y=78 | | xy=-40 | | ax+5x-4=10 | | 4-4x^2+4xy-y^2= | | 15-1/2x=1/4x | | x/5-x/3=8/15 | | 5/8+(-7/12) | | -4/7+2/7 | | 4x-7y=29 |

Equations solver categories